2009
DOI: 10.2308/aud.2009.28.1.137
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Assurance on Voluntary Nonfinancial Disclosure: An Experimental Evaluation

Abstract: SUMMARY: This study examines whether assurance on the voluntary provision of nonfinancial performance indicators affects the stock price estimates of a group of sophisticated financial report users. We conducted an experiment where participants were provided with a case study containing excerpts from a hypothetical company's annual report. Nonfinancial performance and assurance were manipulated in a 2 (positive and negative nonfinancial performance indicators) ×2 (assurance and no assurance) +1 (control condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
136
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(152 citation statements)
references
References 22 publications
14
136
0
2
Order By: Relevance
“…Several experimental studies consistently found a positive effect of sustainability assurance on the perceived reliability of the respective information for report users (BrownLiburd & Zamora, 2015;Hodge, Subramaniam, & Stewart, 2009;Pflugrath, Roebuck, & Simnett, 2011). This effect, however, seems to be context-specific and more pronounced when sustainability-related performance is positive (Brown-Liburd & Zamora, 2015;Coram, Monroe, & Woodliff, 2009). Ultimately, such increased perceived reliability and credibility can even translate into higher stock price estimates (Coram et al, 2009).…”
Section: Literaturementioning
confidence: 96%
See 1 more Smart Citation
“…Several experimental studies consistently found a positive effect of sustainability assurance on the perceived reliability of the respective information for report users (BrownLiburd & Zamora, 2015;Hodge, Subramaniam, & Stewart, 2009;Pflugrath, Roebuck, & Simnett, 2011). This effect, however, seems to be context-specific and more pronounced when sustainability-related performance is positive (Brown-Liburd & Zamora, 2015;Coram, Monroe, & Woodliff, 2009). Ultimately, such increased perceived reliability and credibility can even translate into higher stock price estimates (Coram et al, 2009).…”
Section: Literaturementioning
confidence: 96%
“…This effect, however, seems to be context-specific and more pronounced when sustainability-related performance is positive (Brown-Liburd & Zamora, 2015;Coram, Monroe, & Woodliff, 2009). Ultimately, such increased perceived reliability and credibility can even translate into higher stock price estimates (Coram et al, 2009). Experimental research on integrated reporting, however, is still very scarce.…”
Section: Literaturementioning
confidence: 99%
“…According to Bagnoli et al [52], by means of the assurance process, managers determine ex ante their level of social responsibility, entrusting the assurer with the certification of the actual level achieved. Via these activities, managers aim to eliminate negative perceptions, for example arising from greenwashing, thus reinforcing the confidence and loyalty of shareholders [44,53].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As mentioned in Section 2, non-financial disclosure is increasingly relevant for auditors and accountants for their decision-making processes [69]. We argue that higher levels of ICD should reduce the level of the audit risk, as auditors have more information as basis for their evaluations, due to the firms' propensity to be more transparent [7,70].…”
Section: Hypotheses and Research Questionsmentioning
confidence: 99%